(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2026)
This article analyzes, from the perspective of legal pragmatism, the structural inconsistency of the evidentiary model required for granting special retirement benefits in Brazil, particularly regarding the requirement that the insured party submit documents that are the employer’s responsibility to produce. To this end, the study draws upon the consequentialist and anti-foundationalist strands of pragmatism – based on the works of authors such as Richard Posner and John Dewey – to demonstrate how evidentiary rigidity undermines the effectiveness of the fundamental right to social security. Regarding methodology, a deductive approach is adopted, utilizing qualitative research based on a review of literature and case law. The analysis focuses on specific rulings by the Federal Regional Court of the 3rd Region, highlighting a contradiction between the formality of documentary requirements and the social reality of workers. The study concludes that overemphasizing technical forms as the sole form of evidence constitutes a substantive injustice, violating the constitutional principles of human dignity, due process of law, and social protection